2014
DOI: 10.1021/es5036333
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable Constituents of Thirdhand Tobacco Smoke: Chemical Characterization and Health Impact Considerations

Abstract: Tobacco smoke residues lingering in the indoor environment, also termed thirdhand smoke (THS), can be a source of long-term exposure to harmful pollutants. THS composition is affected by chemical transformations and by air−surface partitioning over time scales of minutes to months. This study identified and quantified airborne THS pollutants available for respiratory exposure, identified potential environmental tracers, and estimated health impacts to nonsmokers. In a ventilated 18 m 3 laboratory chamber, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
125
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 38 publications
12
125
0
Order By: Relevance
“…Meanwhile, levels of the substance deposited on furniture surfaces did not differ between smoking and non-smoking rooms in the hotels 43 . The only semi-volatile amine found in the gaseous phase two hours after burning the cigarette was 3-EP, but it later disappeared (at 18 hours), probably due to the high adsorption to surfaces 55 .…”
Section: Ths Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, levels of the substance deposited on furniture surfaces did not differ between smoking and non-smoking rooms in the hotels 43 . The only semi-volatile amine found in the gaseous phase two hours after burning the cigarette was 3-EP, but it later disappeared (at 18 hours), probably due to the high adsorption to surfaces 55 .…”
Section: Ths Compositionmentioning
confidence: 99%
“…Sleiman et al 55 suggested that chlorinated compounds and chloride ions could react and form chloromethane and dichloromethane, two substances that are not usually present in ETS. Pesticide residues in tobacco and in the bleaching agents used in cigarette paper are the probable sources of these chlorinated compounds.…”
Section: Ths Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…More and more attention is paid to the problem of ''indirect'' smoking, i.e., secondhand smoking (SHS), but also third-hand smoking (THS) (WHO 2010; US Department of Health and Human Services 2006;Hu and DesMeules 2007;IARC 2004;State of California EPA 2005;Nebot et al 2009;Matt et al 2011;Petrick et al 2011;Sleiman et al 2014;Al-sarraf et al 2015). This problem refers not only to traditional cigarettes, but to e-cigarettes (Flouris et al 2013;Stillman et al 2015;Czogała et al 2014) as well.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the possibility for reemission of sorbed pollutants from fabrics is high, causing adverse health effects. Recent studies showed that exposure to smoke fume constituents reemitted from fabrics, 39 defined as third-hand smoke, could cause significant genetic damage in human cells. 40 Faulde et al 35 reported that untreated fabrics were crosscontaminated by permethrin-impregnated uniforms during storage, whether contact was direct or indirect.…”
Section: ■ Introductionmentioning
confidence: 99%